Culinary Products Competitiveness with Functional Purpose - Mykhailo Peresichnyi (Ресторанний і готельний консалтинг: Інновації, 2019)
Relevance. Under market conditions, product competitiveness is a dynamic phenomenon. Originality and uniqueness of production can increase its competitiveness, and with the help of patenting to protect and extend. The production of health food products, including cereal dishes, which ensure the stability of the physical, people’s physiological and metabolic conditions, it is recognized as a promising and relevant direction of the domestic restaurant industry development. The harmonious combination of high taste, nutritional value and therapeutic and prophylactic orientation provides an increase in demand for products from cereals of functional purpose in the domestic market. At the stages of developing new technologies, it became necessary to assess the products competitiveness, which in modern conditions is the main factor for success in the market or in a particular segment. Taking this into account, a method of modeling promising competitive culinary products of the functional purpose “Krupenik with Fiber” using micronized grain, miprovit and soy fiber 70% was proposed.